Analisis Usaha Pembuatan Tahu (Studi Kasus pada Pabrik Tahu “Berkat Sekumpul” Martapura) - Fitriani Fitriani; Ana Zuraida; Siti Erlina (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2013)
The study aims to determine the feasibility (RCR) and the break-even point (BEP) of tofu making business. The method used is a case study on